Credit participation and constraints of the poor in peri-urban areas, Vietnam: a micro-econometric analysis of a household survey - Doan, Tihn; Quang Tuyen, Tran (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
This paper uses a dataset collected from peri-urban areas of Ho Chi Minh City, Vietnam to examine how the poor use their loans, and factors affecting their credit participation and credit constraints. The paper finds that the presence of many commercial banks in the areas does not help the poor, instead the poor rely heavily on informal credit. Loans in the periurban areas are mainly used for non-productive purposes, which stresses the importance of consumption smoothing. Better community relationships and interpersonal trust in morerural wards help households to access to credit. In urban areas, the poor rely more upon subsidized funds. A closer look at specified microcredit sources reveals that household behaviour differs in each market segment. Furthermore, the poor are highly credit-constrained. Wealthier-asset households among the poor appear to be less credit-constrained. The likelihood of credit constraints increases with the distance to the nearest banks, which suggests that credit supplyside intervention could help overcome credit constraints. Overall, the poor in urban areas are more credit-constrained because of exclusion by commercial banks and weaker interpersonal trust
Argumenta Oeconomica, 2015, Nr 1 (34), s. 175-200
Keywords: Credit participation; credit constraints; the poor; peri-urban; Vietnam